Prognostic significance of tissue Doppler imaging–derived myocardial performance index in pediatric patients with dilated cardiomyopathy. (10th November 2019) - Wright, Lydia K.; McGaughy, Falon; Kellerman, Michael; Border, William L.; Sachdeva, Ritu
Abstract: TDI–MPI has been shown to predict cardiovascular mortality in adults; there are a paucity of data on its use in children. We sought to determine the prognostic significance of TDI‐MPI at time of DCM diagnosis in children. Patients aged ≤18 years diagnosed with DCM were included along with age‐ and sex‐matched controls. Echo at diagnosis was analyzed to obtain standard measures of LV function, PW‐MPI, and septal and LV free wall TDI‐MPI. Survival analysis was used to assess the time to composite outcome of death, VAD, or transplant, stratified by TDI‐MPI z ‐score. The study included 79 patients with DCM and 79 controls. During a median follow‐up of 182 days (IQR 41‐815 days), 16 underwent VAD placement, 21 underwent cardiac transplant, 6 died, and 36 had event‐free survival. The median septal TDI‐MPI for cases was 0.70 for patients with DCM vs 0.45 for controls ( P  < .001). Those with septal TDI‐MPI z ‐scores ≥2 develop events significantly earlier than those with z ‐score <2 ( P  = .014). In multivariable analysis, TDI‐MPI z ‐score ≥2 was significantly associated with poor outcomes (HR 2.12, 95% CI 1.06‐4.23). TDI‐MPI can be reliably performed in pediatric patients with DCM. A TDI‐MPI z ‐score ≥2 at diagnosis may be associated with earlier poor outcome. Further studies evaluating the use of TDI‐MPI in longitudinal follow‐up of patients with DCM may be helpful in refining its clinical use.